Positive circumferential resection margins following locally advanced colon cancer surgery: Risk factors and survival impact. Issue 3 (18th December 2019) - Goffredo, Paolo; Zhou, Peige; Ginader, Timothy; Hrabe, Jennifer; Gribovskaja‐Rupp, Irena; Kapadia, Muneera; You, Y. Nancy; Hassan, Imran
Abstract: Background: While the prognostic implications of positive circumferential resection margins (CRM) have been established for rectal cancer, its significance in colon cancer has not been well defined. The aim of the current study was to determine national rates for positive CRM in locally advanced colon cancer, associated factors, and survival impact. Methods: The National Cancer Database was queried to identify patients with stage II‐III adenocarcinoma of the colon (2004‐2015). Results: Positive CRM was identified in 9% of stage II and 12% of stage III patients. Factors associated with negative CRM included surgery in a high‐volume facility, adequate lymph‐node harvest, and negative distal/proximal margins. No difference in CRM rates was observed between surgical approaches, although having a positive CRM was significantly associated with higher conversion rates. Positive CRM was associated with significantly lower overall survival on both univariate and multivariable analysis. Conclusions: Positive CRM rates exceeded 10% nationally and have an adverse impact on survival. While several tumor characteristics were identified as independent risk factors, oncologic resections and surgery at high‐volume centers were associated with lower rates of positive CRM. These findings emphasize the need for process improvement initiatives targeting modifiable factors, including adoption of appropriate oncologic techniques, standardized pathology reporting, and potential neoadjuvant strategies.